The behavioral intention of micro enterprises to use the integrated Qardhul Hasan and equity-based microenterprise development (IQEMD) model as a source of financing - Haqbin, Naqibullah; Mohd Thas Thaker, Mohamed Asmy (Emerald Publishing, 2025)
Purpose – This study proposes the integrated Qardhul Hasan and equity-based microenterprise development (IQEMD) model, a financial model for microenterprises in Muslim nation such as Afghanistan. This study aims to overcome the significant challenges these businesses face in securing financial resources, offering a tailored, sustainable solution to enhance their operations. Design/methodology/approach – This study collected primary data via a survey from 466 microentrepreneurs in Kandahar, Afghanistan. Data analysis was performed using partial least squares with SmartPLS 4 software. The study’s validation of the proposed financial model among microenterprises was grounded in the theory of reasoned action, ensuring a solid theoretical basis for its findings. Findings – The findings of this research revealed that the attitudes and subjective norms of Afghan microentrepreneurs positively influence their intention to use IQEMD Model. These findings provide important guidance for financing ventures and policymakers, highlighting the IQEMD model’s potential to improve financial strategies and practices for microenterprises in Afghanistan. Research limitations/implications – This study focuses solely on microenterprise development in Afghanistan, with its sample size and study area being clear constraints. Therefore, caution is advised when interpreting the results, which may not be broadly applicable. The reliance on current factors may also restrict the exploration of other important determinants affecting microenterprises’ behavioral intentions toward using the IQEMD model. Future research should consider incorporating new factors to optimize the IQEMD model and include interviews with more stakeholders to increase its validity. Practical implications – The findings of this paper offer microenterprises an alternative source of financing to start or expand their businesses. This study holds implications for government and policymakers. By incorporating a nonprofit organization as suggested in this model, it assists the government in reducing expenditures associated with the development of microenterprises. Originality/value – This study is a pioneering effort in merging Qardhul Hasan and equity-based financing for microenterprise development. It significantly contributes to existing research by underscoring the effectiveness and impact of such financing as a viable source for these enterprises. These strategies could notably boost productivity, employment and gross domestic product growth. The study enhances understanding of alternative financing models in the microenterprise sector.